THE INFLUENCE OF THERAPEUTIC MODALITIES ON THE FUNCTIONAL ABILITY OF PATIENTS WITH RHEUMATOID ARTHRITISon the functional ability of patients with rheumatoid arthritis - Krstić, Nikola; Kostić, Ivana; Petronijević, Ana; Damnjanović, Ivana (Acta medicae Medianae, 2022)
Rheumatoid arthritis (RA) is a chronic, systemic inflammatory disease. The progres-siveness of the disease and damage to the joints caused by RA can make a significant impact on the functioning ability. The gold standard for assessing functional status in RA is the HAQ questionnaire. The aim of the study was to assess the impact of sociodemographic characteristics, laboratory parameters of interest and therapeutic modalities on the functional ability of patients with RA. A retrospective cross-sectional study involved 109 patients, 29 male and 83 female, with a diagnosis of RA. Data on the demographic and clinical characteristics of the patients, laboratory findings and applied therapeutic modalities were collected. Microsoft Office Excel and PASW were used for statistical analysis. An estimation error level of less than 5% (0.05) was used as the statistical significance threshold. The results of the study indicate that more than a third of the participants have a HAQ-DI greater than 1, which indicates a significant decrease in functional ability. The largest number of subjects with a high HAQ-DI index (41.2%) was observed in the group of subjects who used glucocorticoids in combination with several synthetic disease-modifying drugs (GC + multiDMARD). The values of HAQ-DI differ statistically significantly in relation to the applied therapeutic modalities (p = 0.004). HAQ-DI significantly correlated with the values of sedimentation rate (p < 0.05), CRP (p < 0.01) and anti-CCP (p < 0.05). PLUM regression analysis showed that functional ability was impaired in the group of subjects without and with a smaller number of comorbidities. In addition, the results of regression analysis indicate that the therapeutic modalities GC +methotrexate (p = 0.023) and GC + multiDMARD (p = 0.002) can significantly contribute to better functional ability in patients with RA. Methotrexate, alone or in combination with other drugs, can significantly contribute to better functional ability and is effective in the treatment of most patients with RA.